(untitled) (Nepal Journal of Sociology, 2025)
This study explores the liminal dynamics of language, identity making, and diasporic experiences among Nepali communities, both within Nepal and abroad. Using an anthropological approach, historical analysis, and theoretical linguistic frameworks, the study examines how English functions as a marker of upward mobility in Nepal, contrasting with the cultural languages that gain symbolic capital in the diaspora. It challenges the dominant narratives that conceive diasporic identity through nostalgic or passive lenses. Instead, it analyses the multiplicity of inhabitance, employing Lebanese anthropologist, Ghassan Hage’s concept of “diasporic lenticularity,” to assert that diasporic Nepaliness is plural, present, and fragmented yet cohesive. Relying on this framework, this study argues that the valorization and marginalization of English and vernaculars shape identity navigation in both spaces. Language is not merely a tool for communication but a vehicle for negotiating belonging, agency, and legitimacy in a transnational context. Drawing upon cases from interviews, media, and educational discourse, this study situates Nepali identity as translingual and multiply inhabited across space and time.